2021
DOI: 10.1016/j.ijcha.2021.100893
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Amulet and Watchman left atrial appendage closure devices: A real-world, single center experience

Abstract: Background Data reporting a head-to-head comparison between Amulet and Watchman devices are scarce. The aim of this study was to compare the Watchman™ versus Amulet™ left atrial appendage closure (LAAC) devices in a consecutive, industry-independent registry. Methods Patients who underwent LAAC using Watchman or Amulet devices from January 2014 to December 2019 at the University Heart Center Lübeck, Lübeck, Germany were included in the present analysis. Primary endpoint… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…A total of 2926 patients from seven studies (Table 2) 12,[15][16][17][18][19][20] underwent LAAO, with a total of 1508 patients in the Watchman 2.5 group and 1418 patients in the Amplatzer Amulet group included in the meta-analysis (Figure 1 and Table 2). Seven total studies, including TA B L E 1 Quality assessment of included studies by NOS…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 2926 patients from seven studies (Table 2) 12,[15][16][17][18][19][20] underwent LAAO, with a total of 1508 patients in the Watchman 2.5 group and 1418 patients in the Amplatzer Amulet group included in the meta-analysis (Figure 1 and Table 2). Seven total studies, including TA B L E 1 Quality assessment of included studies by NOS…”
Section: Resultsmentioning
confidence: 99%
“…Lakkireddy 2021, 12 Saad 2021, 20 and Radinovic 2021 19 which scored 8 points on the Newcastle-Ottawa Scale (Table 1), and Mansour 2021, 18 Chen 2019, 15 Fastner 2018, 16 and Kefer 2018 17 scored 7 points on the Newcastle-Ottawa Scale (Table 1), indicating good quality. A descriptive comparison of the baseline characteristics and follow-up durations is shown in Table 2.…”
Section: Follow Up Adequacy Scorementioning
confidence: 99%
See 1 more Smart Citation
“…Saad et al also reported that periprocedural complications were higher in ACP device than in Watchman device. But the efficacy and safety between Watchman and ACP devices were comparable during the long-time follow-up (median follow-up durations of Watchman and ACP devices were 238 and 160 days, respectively) ( 17 ). The efficacy and safety were also comparable between Watchman and ACP devices during our long-term follow-up, but procedure-related complications were comparable between Watchman and ACP devices in our center ( Supplementary Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…For ACP and its second-generation, Amulet, multiple retrospective and prospective registries have reported successful device implantation in 95–100% of patients, with a low rate of major periprocedural adverse events. A recently published, industry-initiated, large, randomized, multi-center, trial (Amulet IDE trial), evaluating the safety and effectiveness of the Amulet occluder compared with the Watchman™ device, has shown that the Amulet occluder was non-inferior to safety and effectiveness of stroke prevention compared with the Watchman device ( 34 ). In light of the results of these trials, ESC guidelines suggest LAA closure, for stroke prevention, in patients with AF and contraindications for long-term anticoagulant treatment, e.g., intracranial bleeding without a reversible cause (class of recommendation IIb, level of evidence B) ( 35 ).…”
Section: Laa Anatomy and Indication For Closurementioning
confidence: 99%